The use case and smart grid architecture model approach : the IEC 62559-2 use case template and the SGAM applied in various domains /: the IEC 62559-2 use case template and the SGAM applied in various domains. (2017) - Gottschalk, Marion; Uslar, Mathias; Delfs, Christina
No abstract available